Genetic parameters and selection indices for a population of Pinus elliottii Engelm. var. elliottii - Pswarayi, I; Idah Zviripayi Pswarayi (1993)
﻿ P. elliottii Engelm. var. elliottii is an important exotic plantation species in Zimbabwe, where it is grown for saw-timber and resin production. Three progeny tests, originating from factorial matings between parents selected in plantations, were assessed at five, eight and 15 years. The objectives of the study were to characterise quantitative genetic variation in the population through the estimation of genetic parameters, and to use these parameters in combined indices to select for specified breeding objectives for P. elliottii in Zimbabwe. All traits of interest were under a reasonable degree of additive genetic control, and the magnitudes of nonadditive genetic variances were almost invariably much less than those of additive genetic variances. Narrow-sense heritabilities for growth traits, wood density and resin yield were moderate to high, ranging from 0.3 - 0.42; those for stem straightness and branching traits were lower, ranging between 0.10 and 0.25. Genetic correlations at each of the assessment ages were more variable; of most consequence for this study were the slight negative correlations between wood density and both stem diameter and volume, and the slight positive correlation between density and height. Age-age correlations for growth traits were high, indicating potential for early selection. Age-age correlations for other traits ranged from moderately negative to highly positive. Although statistically significant for many traits, genotype-environment interaction was judged by a number of criteria to be of little practical importance. No one site was the most efficient for selection across the range of traits for establishment at other sites; rather, a set of pooled parameters was estimated for application on sites typical of those on which commercial plantations of P. elliottii are established. Selection indices were constructed for four breeding objectives, representing differing assumptions about the relative importance of saw-timber and resin production. Indices for both direct and indirect selection were compared in terms of genetic gain, efficiency and accuracy, which were influenced by the differential weighting of traits in the breeding objective. The highest gains, efficiency and accuracies were for the breeding objective of saw-timber only; increasing the emphasis on resin production reduced each of these parameters, and also had a more adverse impact on wood density. For a breeding objective corresponding to or emphasizing saw-timber production, selection based on diameter or height at five years was best; selection on the latter has the advantage of maintaining wood density at around its present level. Should resin production also be important, resin yield or a correlated trait must be included in the index. Efficiencies of indirect selection were highest at five years, regardless of the breeding objective or selection criteria considered. The lack of economic information was a considerable hinderance in conducting these analyses. The construction of more complete indices, incorporating information from all siblings represented in the factorial mating design, was also investigated for the breeding objective of saw-timber production. These indices were compared in terms of gain and accuracy, and their effect on population structure in the subsequent generation. Selection based on the most complete index resulted in the greatest gain and accuracy, but also in the greatest reduction in additive genetic variance in the next generation. These results highlight the dilemma facing breeders charged both with achieving gains in the short term and maintaining diversity over the longer term. Breeding strategies which facilitate differential intensities of selection and breeding, and the maintenance of a large effective population size, are seen as the best means to resolve these conflicting demands; some implications for the breeding population of P. elliottii in Zimbabwe are discussed.